2019
DOI: 10.1038/s41467-019-10192-2
|View full text |Cite
|
Sign up to set email alerts
|

The viral protein corona directs viral pathogenesis and amyloid aggregation

Abstract: Artificial nanoparticles accumulate a protein corona layer in biological fluids, which significantly influences their bioactivity. As nanosized obligate intracellular parasites, viruses share many biophysical properties with artificial nanoparticles in extracellular environments and here we show that respiratory syncytial virus (RSV) and herpes simplex virus type 1 (HSV-1) accumulate a rich and distinctive protein corona in different biological fluids. Moreover, we show that corona pre-coating differentially a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 65 publications
7
161
0
Order By: Relevance
“…Herpes simplex virus-type 1 (HSV-1) infection is a well-recognized risk factor of AD [102,103]. HSV-1 induces AD via affecting multiple AD events, such as through enhancing Aβ 1−42 production [104]. The virus causes DSB accumulation in rat cortical neuron through downregulation of Ku80, an essential component of NHEJ ( Figure 2), and thus impairs NHEJ in cortical neurons [105].…”
Section: Link Of Nhej In Admentioning
confidence: 99%
“…Herpes simplex virus-type 1 (HSV-1) infection is a well-recognized risk factor of AD [102,103]. HSV-1 induces AD via affecting multiple AD events, such as through enhancing Aβ 1−42 production [104]. The virus causes DSB accumulation in rat cortical neuron through downregulation of Ku80, an essential component of NHEJ ( Figure 2), and thus impairs NHEJ in cortical neurons [105].…”
Section: Link Of Nhej In Admentioning
confidence: 99%
“…(C) A schematic representation of HEN where an exogenous surface catalyze amyloid nucleation via binding, concentrating, and inducing conformational changes in the bound peptides/proteins, which facilitate amyloid transformation. (D) A negatively stained transmission electron microscopy picture demonstrating direct interaction between the surface of a virus (HSV-1) and a growing amyloid protofilament of Aβ 1-42 peptide (unpublished image from the viral catalyzed nucleation experiments performed in the study of Ezzat et al (2019), where HSV-1 was incubated with 50 µM Aβ 1-42 for 100 min. at 37 • C).…”
Section: Amyloid Nucleation Mechanismsmentioning
confidence: 99%
“…aggregation via HEN. This includes microbial surfaces (Bantle et al, 2019;Ezzat et al, 2019), lipid vesicles (Habchi et al, 2018), and nanoparticles (Linse et al, 2007). Additionally, polymer surfaces such as glycosaminoglycans (GAGs) (Iannuzzi et al, 2015) and nucleic acids (Liu and Zhang, 2011) have been shown to accelerate amyloid aggregation.…”
Section: Amyloid Nucleation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also showed that HSV-1, which has been implicated in Alzheimer's disease, catalyzes the nucleation and accumulation of the Aβ42 peptide both in vitro and in vivo. Results from Ezzat et al, (2019) showed that unlike the viral genome coded surface proteins, the viral protein corona is an acquired structural layer that is dependent on the viral microenvironment resulting in different viral identities based on the target tissue and the target organism. Additionally, the viral coronadriven heterogeneous nucleation of amyloids illustrates convergence between viral and amyloid pathologies suggesting a direct physical mechanistic link that warrants further investigation.…”
Section: Ebola Virus Viral Protein Corona and Arbovirusesmentioning
confidence: 99%